Household Saving Behaviour in District Peshawar, Khyber Pakhtunkhwa - Ruqqia; Dr. Fariha Sami; Ur Rahman, Sami (Journal of Business & Tourism, 2023)
The main purpose of this study is to examine household saving behaviour in the district of Peshawar Khyber Pakhtunkhwa. Data for this study was conducted through a survey questionnaire and questionnaires were distributed among 400 households of district Peshawar town III. The data was analyzed through the ordinary least square method using SPSS 26. Weighted least square (WLS) was used for estimation. The study explored that there is a strong link between household savings and planned variables. The results show that the total income of households has a direct and significant relationship with the savings of the households, so the result goes with the Keynesian theory of income and saving. Furthermore, a number of adult equivalence and debt have positive and significantly related to household saving in district Peshawar, whereas the dependency ratio has a negative but significant relationship with household saving in the study area which means that when a number of dependents in a family increases the rate of saving of that family decreases. The study suggests that the government of Khyber Pakhtunkhwa should increase employment opportunities for those who depend on their family.